An Examination of Cameroonian Preservice Biology Teachers’ Conceptualisation of Living Organisms from philosophical and Epistemological Perspectives - Nchia , Lawrence Ntam (Journal of Education and Practice, 2025)
Purpose: This study investigates the conceptualisation of living organisms among 53 preservice biology teachers at the Higher Teacher Training College in Yaoundé, Cameroon. Methodology: Drawing from historical and contemporary paradigms, such as animism, vitalism, finalism, determinism, evolutionism, and interactionism, the research seeks to identify dominant conceptions and epistemological obstacles. A cross-sectional descriptive survey design was used on a convenient sample of 53 student teachers. Findings: Results revealed that 83% of respondents had scientifically correct interactionist conception of living organisms. However, the study nobserved the coexistence of historical and modern paradigms, with persistent epistemological obstacles such as finalism (69.8%) and animism (46.5%) affecting their understanding. One way ANOVA showed no statistically significant differences in the conceptualisation of living organisms based on sex and academic levels. Additionally, bivariate correlation revealed mixed conceptions, as the dominant interactionist view had a statistically significant, strong, and positive correlation with other historical and contemporary conceptions. Unique Contribution to Theory, Policy and Practice: The study contributes to theory by highlighting epistemological obstacles in preservice biology teachers’ understanding of living organisms and reinforces the role of the Nature of Science (NOS) framework in promoting conceptual change. It informs policy by advocating for curriculum reforms that incorporates epistemological reflexivity and interdisciplinary approaches in teacher education. In practice, it emphasizes active learning strategies, explicit NOS instruction, and continuous professional development to improve teachers' conceptual clarity and instructional effectiveness in biology education. The study highlights the need for targeted educational reforms to promote a scientifically accurate and integrative understanding of biological concepts among preservice teachers.